Thoughts, images, and appraisals associated with acting and not acting on the urge to self-injure - McEvoy, Peter; Hayes, Sarra; Hasking, Penelope; Rees, Clare (Elsevier BV; North Holland, 2017)
Objectives The aim of this study was to examine the frequency, content, and appraisals of thoughts and images occurring during urges to engage in non-suicidal self-injury (NSSI). Method Undergraduates (N = 154) with a history of NSSI completed an online survey of their thoughts, images, and appraisals when they acted on urges to engage in NSSI as well as when they resisted urges to self-injure. Results Most (>90%) participants reported experiencing both thoughts and images during urges to engage in NSSI. During urges that resulted in self-injury, self-critical and hopeless thoughts were most distressing, and thoughts about relief from emotional distress were most comforting. Images of the anticipated injury were most common. During urges that did not result in self-injury themes of the futility of NSSI, positive self-talk, and the impact on others were most common. Images were most frequently of the negative impact on self and others, and the anticipated injury. Appraisals encouraging NSSI occurred when individuals did and did not act on their urges, but concurrent strong discouraging appraisals appeared to be protective on occasions when urges did not result in self-injury. Limitations Retrospective self-report was used to assess cognitive content. Generalisability of findings to non-student samples needs to be assessed. Conclusions Findings from this study may inform comprehensive assessment of thoughts and images associated with urges to engage in NSSI. NSSI interventions may need to promote thoughts, imagery and appraisals that discourage NSSI whilst simultaneously modifying cognitions that encourage NSSI.